Necrotic Sequelae of COVID-19 Vasculitis in Geriatric Patient - Jamalludin, Amira Nabiha; Che Din, Nur Amalina Binti (International Journal of Human and Health Sciences (IJHHS), 2021)
COVID-19 vasculitis has recently been reported in COVID-19 articles. Cutaneous manifestations can progress to necrotic skin lesion in 6% of cases. This is theoretically linked with advanced age and severe degree of infection. (1) This is a case of a 90-year-old female from a care home with a background history of dementia, heart failure, hypothyroidism, diabetes and pacemaker-in-situ. She presented with fever and tachycardia. COVID-19 test turned out positive. Electrocardiogram (ECG) showed atrial fibrillation with rapid ventricular response of spontaneous resolution. Several days later, she had recurrent supraventricular tachycardia which was resolved by adenosine. The day after, she developed multiple petechiae on hands, feet and nose. Among differentials made were infective endocarditis, heparininduced thrombocytopenia and idiopathic thrombocytopenic purpura. Full blood count revealed thrombocytopenia with p-anca positive on vasculitis screen. The lesions progressed into necrotic skin breakdown, which was unaesthetically pleasant for the patient. Final diagnosis by a Geriatrician was COVID-induced vasculitis. Multidisciplinary team (MDT) consisted of Cardiology, Haematology, Dermatology, Rheumatology and Plastic Surgery were involved in decision-making for investigations and treatment. COVID-19 vasculitis in this case possibly augmented by other factors. The pre-existing heart failure may act as cardiovascular risk factor, predisposing to systemic vascular failure thus intensifies thrombosis. (1) Besides that, can it be aggravated by hypothyroidism whereby autoimmunity is the precursor? This case holds impactful clinical significance, opening doors to future research and audit. MDT involvement is highly valued thus magnifying quality of patient care and safety. Together with comprehensive geriatric assessment where physical, functional, mental, social and environmental factors are taken into management. International Journal of Human and Health Sciences Supplementary Issue-2: 2021 Page: S10